Body mass index is associated with the antidepressant effects of intravenous ketamine in patients with depression - Tan, Jian-Qiang; Gu, Li-Mei; Zhou, Yan-Ling; Wang, Cheng-Yu; Lan, Xiao-Feng; Zheng, Wei; Ning, Yu-Ping (Frontiers in Psychiatry, 2025)
ObjectivesWe aimed to explore the correlation between baseline body mass index (BMI) and the antidepressant properties of intravenous ketamine in patients with depression.MethodsWe divided 135 patients diagnosed with either major depressive disorder (n=103) or bipolar depression (n=32) into lower and higher BMI groups based on their baseline BMI. Patients with a lower BMI (BMI<24 kg/m²; n=92) were included in the lower BMI group, and those with a higher BMI (BMI≥24 kg/m²; n=43) were assigned to the higher BMI group. Each participant received six ketamine infusions. Antidepressant remission was determined using a Montgomery–Åsberg Depression Rating Scale (MADRS; total score of ≤10) within 24 hours after the sixth ketamine infusion on day 13. Antidepressant response was characterized by a ≥50% alleviation in the symptoms of depression at the same time point. Changes in symptoms of depression over time were assessed using a linear mixed model.ResultsThe antidepressant response rate in the higher BMI group (67.4%, 95% confidence interval [CI]: 53.5%–81.4%) was higher than that in the lower BMI group (51.1%, 95% CI: 41.3%–60.9%). In addition, the remission rate was higher in the higher BMI group (39.5%, 95% CI: 25.6%–55.8%) than in the lower BMI group (31.5%, 95% CI: 21.7%–41.3%). However, these differences were not significant (all P>0.05). The linear mixed models with covariates indicated a significant group-by-time interaction in the MADRS scores (F13, 1729=3.0, P<0.001). A significant correlation was found between baseline BMI level and the change in depressive symptoms on days 13 and 26 (all P<0.05). However, these correlations were not significant after Bonferroni correction or controlling for baseline depressive symptoms (all P>0.05).ConclusionOur exploratory, post-hoc analysis of an open-label, single-arm study suggests that patients with depression and a higher baseline BMI may experience greater reductions in depressive symptoms compared with those with a lower baseline BMI after receiving six ketamine infusions.